2010
DOI: 10.1002/jcc.21702
|View full text |Cite
|
Sign up to set email alerts
|

The charge‐transfer states in a stacked nucleobase dimer complex: A benchmark study

Abstract: Electronic singlet excitations of stacked adenine-thymine (AT) and guanine-cytosine (GC) complexes have been investigated with respect to local excitation and charge-transfer (CT) characters. Potential energy curves for rigid displacement of the nucleobases have been computed to establish the distance dependence of the CT states. The second-order algebraic diagrammatic construction [ADC(2)] method served as reference approach for comparison to a selected set of density functionals used within the time-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
112
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(121 citation statements)
references
References 82 publications
8
112
1
Order By: Relevance
“…Our results for AT and GC differ from previous calculations at different levels of theory for the same dimers in the B-DNA conformation, with a somewhat shorter stacking distance (3.38 Å here versus 3.15 Å in the preceding references). 45,46 In those cases, no mixing between the charge transfer and the excitonic states is reported. For example, at the EOM-CCSD(T) level of theory, the charge transfer state lies approximately 0.4 eV and 0.6 eV above the exciton states for GC and AT, respectively.…”
Section: Results For the At Gc And Gt Dimersmentioning
confidence: 97%
See 1 more Smart Citation
“…Our results for AT and GC differ from previous calculations at different levels of theory for the same dimers in the B-DNA conformation, with a somewhat shorter stacking distance (3.38 Å here versus 3.15 Å in the preceding references). 45,46 In those cases, no mixing between the charge transfer and the excitonic states is reported. For example, at the EOM-CCSD(T) level of theory, the charge transfer state lies approximately 0.4 eV and 0.6 eV above the exciton states for GC and AT, respectively.…”
Section: Results For the At Gc And Gt Dimersmentioning
confidence: 97%
“…Such charge transfer states have been invoked in previous experimental and computational studies on DNA spectroscopy. 17,22,24,26,27,45 In the stacks AT, GC, and GT, there is a low-lying charge transfer state that mixes with the two locally excited diabatic states. In the AC dimer, the charge transfer character is not so prominent (8% for S 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of MAEs, the best-performing M06-HF through the inclusion of full HF exchange is more broadly applicable than B3LYP and PBE0 to different types of excited states -including Rydberg and charge-transfer states [77,78] that pose a considerable challenge to TD-DFT [52,55,[105][106][107][108]] -this functional is by some margin the least accurate functional for the current benchmark set of low-lying organic valence states. Since the MAE for M06-HF is 0.21 eV larger than the MAE for M06-2X (with 54% HF exchange), which in turn is 0.12-0.16 eV larger than the MAEs for PBE0 (25%) and B3LYP…”
Section: δE 00 Energies With Different Methodsmentioning
confidence: 99%
“…Matsika and coworkers [61] compared the performance of different methods (including CIS, TDDFT, CASSCF, and CC) in the description of excited-state π-stacked nucleobases. A benchmark study by Aquino et al [130] reported stable interbase charge-transfer states for stacked adenine-thymine and stacked guanine-cytosine, the simplest stacked base pairs. However, the nature, and especially the delocalization degree, of the initially populated excited states in real DNA systems remains a puzzle [37].…”
Section: Base Stacking In Dna Strandsmentioning
confidence: 98%
“…In comparisons [122] of three recent LRC functionals, namely BNL [123,124], CAM-B3LYP [125], and LC-PBE0 [126,127], it was found that only CAM-B3LYP gave reasonable energies for the interbase charge-transfer excited states of the hydrogen-bonded Watson-Crick A·T and G·C base pairs. There are also indications that the meta-hybrid M06-HF [128] and M06-2X [129] functionals may be adequate to treat the photoexcitation of nucleobase monomers and oligomers [130]. However, in a systematic excited-state dynamics study of 9H-adenine (Ade), the experimentally observed ultrafast decay was not reproduced in TDDFT-based surface hopping simulations with any of the six tested functionals (PBE, B3LYP, PBE0, CAM-B3LYP, BHLYP, and M06-HF) whereas reasonable decay times were obtained at the ab initio MRCIS and the semiempirical OM2/MRCI levels [131].…”
Section: Density Functional Theorymentioning
confidence: 99%